Sol-gel synthesized Sr4Al14O25:Eu2+/Dy3+ blue-green phosphorous as oxygen sensing materials - DEMİRCİ, SELİM (ELSEVIER SCIENCE BV, 2016)
In this study, we utilized newly synthesized Sr4Al14O25:Eu2+/Dy3+ blue green phosphors along with silver nanoparticles (AgNPs) for fabrication of oxygen sensitive materials. To the best of our knowledge oxygen sensing mechanism of the offered design is totally different from the previously published works. One-component silicone: poly (1-trimethylsilyl-1-propyne), two component phenyl bearing silicone, plasticized polymethylmethacrylate, and ethylcellulose (EC) were tested as matrix materials. Electrospun fibers, porous and smooth thin films were produced by electrospinning or knife coating technique. Oxygen induced luminescence of the phosphors at 544 nm was followed as the analytical signal. Utilization of silver nanoparticles in silicone along with phosphors resulted with a 7.14 fold enhancement in the signal intensity and significant spectral response towards oxygen competing with the signals of the oxygen sensors utilizing metalloporphyrins or ruthenium complexes. We observed high sensitivity and stability, increased surface area and an enhancement in all sensor dynamics. Linearity of the calibration plots was superior for the pO(2) range of 0.0-20.0% with respect to the previously reported ones. When stored at the ambient air of the laboratory there was no significant drift in signal intensity after 12 months. Our sensitivity and stability tests are still in progress. (C) 2016 Elsevier BM. All rights reserved.
Keywords: Blue-green phosphorous; Oxygen; Dissolved oxygen; Sensor; Nano-silver; SILVER NANOPARTICLES; RUTHENIUM COMPLEX; METAL-COMPLEXES; FILTER-PAPER; SENSORS; TEMPERATURE; SILICA; GADOLINIUM(III); EUROPIUM(III); PORPHYRIN